Diversity, expression, and structural modeling of sugar transporters in Anisakis simplex s. s. L3 and L4 larvae: an in vitro and in silico study - Polak, Iwona; Stryiński, Robert; Paukszto, Łukasz; Jastrzębski, Jan Paweł; Bogacka, Iwona; Łopieńska-Biernat, Elżbieta (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionGlucose transporter (GLUT) research in parasitic nematodes focuses on identifying and characterizing developmentally regulated isoforms, elucidating their regulatory and structural properties, and evaluating their potential as drug targets. While glucose transport mechanisms have been well characterized in the free-living nematode Caenorhabditis elegans, data on parasitic species remain limited. Anisakis simplex s. s., a parasitic nematode, relies on host-derived glucose to maintain energy metabolism. It is hypothesized that A. simplex s. s. utilizes specific glucose transporters to facilitate sugar uptake under varying nutritional conditions.Materials and methodsIn silico analysis identified five putative facilitated glucose transporter genes (fgt-1, fgt-2, fgt-3, fgt-5, fgt-9) and one Sugars Will Eventually be Exported Transporter (sweet-1) gene. The FGTs were classified as members of the solute carrier family 2 (SLC2), while sweet-1 belonged to the SWEET transporter family. Full-length cDNA sequences were obtained, and encoded proteins structurally characterized using bioinformatic modeling. Expression of transporter genes was assessed in A. simplex s. s. larvae at stages L3 and L4 cultured in vitro under different glucose concentrations and time points.ResultsStructural and phylogenetic analyses revealed that fgt-1 and fgt-3 share high similarity with class I GLUTs found in nematodes and vertebrates. Gene expression profiling demonstrated differential regulation between larval stages. Most notably, FGT genes were stably expressed in L4 larvae, whereas in L3 larvae, gene activation was more variable and dependent on glucose concentration, showing a dynamic transcriptional response to nutrient levels. Sweet-1 was expressed in both stages, but its regulation differed over time and with glucose availability. Glucose supplementation altered trehalose and glycogen levels, and trehalase activity varied across stages and treatments, indicating stage-specific metabolic adaptation.DiscussionThe observed transcriptional and biochemical differences between L3 and L4 larvae suggest a shift in glucose uptake mechanisms, from transcuticular absorption in L3 to intestinal glucose uptake in L4 following intestine activation. FGT1 and FGT3 are proposed as key facilitators of glucose uptake, with roles varying across developmental stages. These findings indicate that glucose transporters are regulated in response to changing environmental conditions and may represent targets for rational anthelmintic drug design.